Flexibility vs. Complexity: How Mompreneurs in Makassar Manage Digital Human Resources Amid Dual Identity Dilemmas - Tenri Sayu Puspitaningsih Dipoatmodjo (Abadi Institute, 2026)
This study explores the lived experiences of mompreneurs, mothers who simultaneously manage households and run businesses in Makassar, Eastern Indonesia, with particular focus on how they manage digital human resources (HRM) while navigating the dilemmas of dual identity. Using a qualitative phenomenological approach, the research draws on in-depth semi-structured interviews with 15–20 participants representing a range of digital and hybrid business models. Grounded in five theoretical frameworks women's entrepreneurship theory, work-life balance theory, digital HRM, employee engagement, and adaptive leadership the study reveals that mompreneurs develop creative, resource-constrained HRM practices driven by adaptive intelligence rather than formal systems. Two major themes emerge: (1) divergent HRM strategies across fully digital versus hybrid business models, and (2) persistent emotional tensions arising from dual identity as mothers and business leaders. The findings contribute empirically to debates on gender-responsive digital entrepreneurship in the Southeast Asian context and offer practical implications for local government policy, digital platform design, and peer community development in Eastern Indonesia.